The Enteric Nervous System in Intestinal Inflammation - Keith A Sharkey; Edward J Parr (Canadian Journal of Gastroenterology)
Since about the 1950s nerves in the wall of the intestine have been postulated to play a role in the pathogenesis of inflammatory bowel disease (IBD). Human and animal studies examining the role of nerves in intestinal inflammation are the focus of this review. Consideration is given to two possible ways that nerves are involved in IBD. First, nerves may play a role in the development or maintenance of inflammation through local release of transmitters. Second, once initiated (by whatever means), the processes of inflammation may disrupt the normal pattern of innervation and the interactions of nerves and their target tissues. Many of the functional disturbances observed in IBD are likely due to an alteration in the enteric nervous system either structurally through disruptions of nerve-target relationships or by modifications of neurotransmitters or their receptors. Finally, it appears that the enteric nervous system may be a potential therapeutic target in IBD and that neuroactive drugs acting locally can represent useful agents in the management of this disease.